[PP.07.16] RELATIONSHIP BETWEEN PLASMA RENIN ACTIVITY, PLASMA ALDOSTERONE AND SELECTED ASYMPTOMATIC ORGAN DAMAGE INDICES IN ESSENTIAL ARTERIAL HYPERTENSION. (September 2017) - Pizon, T.; Rajzer, M.; Wach-Pizon, M.; Wojciechowska, W.; Drozdz, T.; Rojek, M.; Czarnecka, D.
Abstract : Objective: To assess the relationship between plasma renin activity (PRA), serum aldosterone concentration (ALDO) and selected asymptomatic organ damage (AOD) indices in mild primary arterial hypertension (AH). Figure. No caption available. Design and method: In 122 patients (61 men and 61 women) with untreated essential AH stage 1 (140/90 > BP < 160/100 mm Hg) and age 30–75 years we measured PRA, ALDO, and selected AOD indices (left ventricular mass index, carotid artery intima media thickness, carotid-femoral pulse wave velocity (cfPWV), central aortic pulse pressure (cPP), estimated glomerular filtration rate (eGFR)). Although the study group included only patients with mild essential AH without typical indications to perform screening for primary aldosteronism we decided to exclude patients with an aldosterone-to-renin ratio (ARR) >100 ng/dl/ng/ml/h and aldosterone concentration >15 ng/dl. Results: Based on PRA results, patients were divided into two subgroups, "low-renin" and "high-renin", according to the Laragh and Alderman criteria (low-renin: PRA < 0.65 ng/ml/h, high-renin: PRA > 0.65 ng/ml/h). Patients with high PRA (>0.65 ng/ml/h) were characterized by lower plasma sodium concentration, several times lower aldosterone-to-renin ratio (ARR), higher ALDO, but similar level of AOD indices compared to patients with low PRA. Among AOD indices, cfPWV (p = 0.04) and cPP (p = 0.019) increased with ARR, while eGFR decreased with ALDO (p = 0.008). After adjusting for age, sex, and BMI, only eGFR was significantly correlated with ALDO (Table 1). In subjects with simultaneously high PRA and ARR values, we found significantly higher cfPWV (p = 0.02) and cPP (p = 0.04) and lower eGFR (p = 0.02) than in those with high PRA but low ARR values. Conclusions: In mild hypertension, assessment of RAAS influence on AOD should include the reciprocal relationship between renin and aldosterone. PRA itself has no predictive value for AOD. More advanced arterial stiffness and renal impairment are associated with increased PRA and ARR. RAAS activity might be useful in AOD prediction and hypertension severity assessment.